Get expert insights and community-driven knowledge on IDNLearn.com. Join our community to access reliable and comprehensive responses to your questions from experienced professionals.
Sagot :
To determine which of the given expressions could not be used to find the exact value of [tex]\(\cos 90^\circ\)[/tex], we need to evaluate each expression separately. We know that [tex]\(\cos 90^\circ = 0\)[/tex]. Therefore, expressions that do not evaluate to 0 cannot be used to determine [tex]\(\cos 90^\circ\)[/tex].
First, recall some trigonometric identities and exact values:
- [tex]\(\sin 45^\circ = \cos 45^\circ = \frac{1}{\sqrt{2}} = \frac{\sqrt{2}}{2}\)[/tex]
- Trigonometric identity: [tex]\(\cos^2 \theta + \sin^2 \theta = 1\)[/tex]
Now, we evaluate each given expression:
### Expression 1: [tex]\(\cos^2(45^\circ) - \sin^2(45^\circ)\)[/tex]
Given:
[tex]\[ \cos^2(45^\circ) - \sin^2(45^\circ) \][/tex]
Substitute [tex]\(\sin 45^\circ = \cos 45^\circ = \frac{\sqrt{2}}{2}\)[/tex]:
[tex]\[ \left(\frac{\sqrt{2}}{2}\right)^2 - \left(\frac{\sqrt{2}}{2}\right)^2 = \frac{2}{4} - \frac{2}{4} = 0 \][/tex]
Thus,
[tex]\[ \cos^2(45^\circ) - \sin^2(45^\circ) = 0 \][/tex]
### Expression 2: [tex]\(2 \sin(45^\circ) \cos(45^\circ)\)[/tex]
Given:
[tex]\[ 2 \sin(45^\circ) \cos(45^\circ) \][/tex]
Substitute [tex]\(\sin 45^\circ = \cos 45^\circ = \frac{\sqrt{2}}{2}\)[/tex]:
[tex]\[ 2 \left(\frac{\sqrt{2}}{2}\right) \left(\frac{\sqrt{2}}{2}\right) = 2 \cdot \frac{2}{4} = 1 \][/tex]
Thus,
[tex]\[ 2 \sin(45^\circ) \cos(45^\circ) = 1 \][/tex]
### Expression 3: [tex]\(2 \cos^2(45^\circ) - 1\)[/tex]
Given:
[tex]\[ 2 \cos^2(45^\circ) - 1 \][/tex]
Substitute [tex]\(\cos 45^\circ = \frac{\sqrt{2}}{2}\)[/tex]:
[tex]\[ 2 \left(\frac{\sqrt{2}}{2}\right)^2 - 1 = 2 \cdot \frac{2}{4} - 1 = 1 - 1 = 0 \][/tex]
Thus,
[tex]\[ 2 \cos^2(45^\circ) - 1 = 0 \][/tex]
### Expression 4: [tex]\(1 - 2 \sin^2(45^\circ)\)[/tex]
Given:
[tex]\[ 1 - 2 \sin^2(45^\circ) \][/tex]
Substitute [tex]\(\sin 45^\circ = \frac{\sqrt{2}}{2}\)[/tex]:
[tex]\[ 1 - 2 \left(\frac{\sqrt{2}}{2}\right)^2 = 1 - 2 \cdot \frac{2}{4} = 1 - 1 = 0 \][/tex]
Thus,
[tex]\[ 1 - 2 \sin^2(45^\circ) = 0 \][/tex]
### Conclusion
From the evaluations above, we see which expressions match [tex]\(\cos 90^\circ = 0\)[/tex]:
- [tex]\(\cos^2(45^\circ) - \sin^2(45^\circ) = 0\)[/tex]
- [tex]\(2 \sin(45^\circ) \cos(45^\circ) = 1\)[/tex]
- [tex]\(2 \cos^2(45^\circ) - 1 = 0\)[/tex]
- [tex]\(1 - 2 \sin^2(45^\circ) = 0\)[/tex]
Therefore, the expression that does not match [tex]\(\cos 90^\circ = 0\)[/tex] is:
[tex]\[ 2 \sin (45^\circ) \cos (45^\circ) \][/tex]
First, recall some trigonometric identities and exact values:
- [tex]\(\sin 45^\circ = \cos 45^\circ = \frac{1}{\sqrt{2}} = \frac{\sqrt{2}}{2}\)[/tex]
- Trigonometric identity: [tex]\(\cos^2 \theta + \sin^2 \theta = 1\)[/tex]
Now, we evaluate each given expression:
### Expression 1: [tex]\(\cos^2(45^\circ) - \sin^2(45^\circ)\)[/tex]
Given:
[tex]\[ \cos^2(45^\circ) - \sin^2(45^\circ) \][/tex]
Substitute [tex]\(\sin 45^\circ = \cos 45^\circ = \frac{\sqrt{2}}{2}\)[/tex]:
[tex]\[ \left(\frac{\sqrt{2}}{2}\right)^2 - \left(\frac{\sqrt{2}}{2}\right)^2 = \frac{2}{4} - \frac{2}{4} = 0 \][/tex]
Thus,
[tex]\[ \cos^2(45^\circ) - \sin^2(45^\circ) = 0 \][/tex]
### Expression 2: [tex]\(2 \sin(45^\circ) \cos(45^\circ)\)[/tex]
Given:
[tex]\[ 2 \sin(45^\circ) \cos(45^\circ) \][/tex]
Substitute [tex]\(\sin 45^\circ = \cos 45^\circ = \frac{\sqrt{2}}{2}\)[/tex]:
[tex]\[ 2 \left(\frac{\sqrt{2}}{2}\right) \left(\frac{\sqrt{2}}{2}\right) = 2 \cdot \frac{2}{4} = 1 \][/tex]
Thus,
[tex]\[ 2 \sin(45^\circ) \cos(45^\circ) = 1 \][/tex]
### Expression 3: [tex]\(2 \cos^2(45^\circ) - 1\)[/tex]
Given:
[tex]\[ 2 \cos^2(45^\circ) - 1 \][/tex]
Substitute [tex]\(\cos 45^\circ = \frac{\sqrt{2}}{2}\)[/tex]:
[tex]\[ 2 \left(\frac{\sqrt{2}}{2}\right)^2 - 1 = 2 \cdot \frac{2}{4} - 1 = 1 - 1 = 0 \][/tex]
Thus,
[tex]\[ 2 \cos^2(45^\circ) - 1 = 0 \][/tex]
### Expression 4: [tex]\(1 - 2 \sin^2(45^\circ)\)[/tex]
Given:
[tex]\[ 1 - 2 \sin^2(45^\circ) \][/tex]
Substitute [tex]\(\sin 45^\circ = \frac{\sqrt{2}}{2}\)[/tex]:
[tex]\[ 1 - 2 \left(\frac{\sqrt{2}}{2}\right)^2 = 1 - 2 \cdot \frac{2}{4} = 1 - 1 = 0 \][/tex]
Thus,
[tex]\[ 1 - 2 \sin^2(45^\circ) = 0 \][/tex]
### Conclusion
From the evaluations above, we see which expressions match [tex]\(\cos 90^\circ = 0\)[/tex]:
- [tex]\(\cos^2(45^\circ) - \sin^2(45^\circ) = 0\)[/tex]
- [tex]\(2 \sin(45^\circ) \cos(45^\circ) = 1\)[/tex]
- [tex]\(2 \cos^2(45^\circ) - 1 = 0\)[/tex]
- [tex]\(1 - 2 \sin^2(45^\circ) = 0\)[/tex]
Therefore, the expression that does not match [tex]\(\cos 90^\circ = 0\)[/tex] is:
[tex]\[ 2 \sin (45^\circ) \cos (45^\circ) \][/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Your search for answers ends at IDNLearn.com. Thank you for visiting, and we hope to assist you again soon.